Long COVID-19–related and non-COVID-19 postviral olfactory dysfunction a comparative MRI study focusing on the olfactory cleft and bulbs - Yifan Li; Yifan Li; Mengfan Liu; Mengfan Liu; Ruoqi Zhang; Ruoqi Zhang; Yibei Wang; Jianfeng Liu; Jianfeng Liu (Frontiers in Neurology)
ObjectiveTo compare the magnetic resonance imaging (MRI) features of the olfactory cleft (OC) and olfactory bulbs (OBs) in patients with long COVID-19-related (LCOD) and non-COVID-19 postviral olfactory dysfunction (NCPVOD) to explore mechanisms underlying persistent olfactory dysfunction.MethodsThis retrospective analysis included patients diagnosed with LCOD or NCPVOD at the China–Japan Friendship Hospital between February 2023 and July 2024. All patients underwent olfactory psychophysical testing (Sniffin’ Sticks), a visual analogue scale (VAS) for olfactory function, and high-resolution MRI scans of the olfactory pathway. MRI features, including OC opacity, OB morphology, OB volume, and olfactory sulcus depth, were compared between groups. Correlations between MRI findings and olfactory test scores were assessed.ResultsSeventy patients were included (35 LCOD, 35 NCPVOD). LCOD patients had significantly higher OC opacity scores than NCPVOD patients (p < 0.001). No significant differences were found in OB morphology, abnormal OB signals, OB volume reduction, or distances between OBs and surrounding structures (p > 0.05). LCOD patients had significantly greater right olfactory sulcus depth than NCPVOD patients (p = 0.026), with negative correlation to age (r = −0.25, p = 0.04). OB volumes positively correlated with TDI and VAS scores.ConclusionLCOD patients exhibited greater OC opacity than NCPVOD patients, suggesting OC inflammation may contribute to persistent olfactory dysfunction. Treating inflammation in the OC could improve long-term olfactory outcomes. OB volume reduction was common in both groups.